KRITIK SANAD DAN MATAN : Telaah Kitab Khulasoh Adz-zahabiyah fi Qawaidi oleh Dr. Tageldin Abbas - Melia Novera; Vina Qurrotu A'yun (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
This paper discusses the method of criticism of Sanad and Matan. In the Hadith studies, both aspects are equally important. Sanad is a series of narrators who convey the hadith, while matan is the content of the hadith itself. To find out the quality of a hadith we must find out the quality of its transmitters and content. Therefore, this paper is important because it discusses the method of criticism of Sanad and Matan. includes the critical methodology of sanad and matan seen in the periods of the Prophet, Companions, Tabi'in, and Tabi' tabi'in. In this study the author uses a historical approach, and in analyzing the data the author uses the descriptive-analysis method. Regarding the critical study of hadith, it has actually been carried out since the time of the Prophet and his companions. However, the criticism of sanad and matan in the initial phase has not been formulated as systematically and methodologically as in the final phase (alMuta`akhirîn). This is because there is still the figure of the prophet as an authoritative source to ask (clarify) the news that friends hear. After the death of the Prophet Muhammad SAW, there have not been many problems in the hadith, apart from that there are still friends who always maintain their honesty and do not want to lie in the name of the Prophet SAW. Criticism of hadith during the time of the Companions focused on testing the truth of whether the Prophet actually conveyed the hadith or not. The source of this paper comes from books/books, and journals that are relevant to the theme of the writing.